Women and authorship in an international journal dedicated to cardiovascular diseases: analysis of the last decade. (3rd October 2022) - Davo-Jimenez, M; Baez Ferrer, N; Igareta-Herraiz, A T; Gonzalez, J; Diaz, R; Avanzas, P; Dominguez-Gonzalez, V; Hernandez-Baldomero, I F; Parra-Esquivel, P C; Garcia-Baute, M C; Hernandez-Vaquero, D; Dominguez-Rodriguez, A
Abstract: Introduction and purpose: Scientific production has become very important in the progression of the healthcare profession, and the studies made in this field reflect a gender gap in the authorship of such production. In the last decade, a review of the publications made over 35 years in 6 high impact factor journals has evidenced a lesser proportion of women among the first and last signing authors (1, 2). Nevertheless, the presence of women as preferential authors is desproportionately low considering the number of female cardiologists in Spain in the year 2017 (40%) (3). The Revista Española de Cardiología (REC) is an international journal dedicated to cardiovascular diseases. Our study investigates the authorship gender differences from publications in the REC. Methods: A cross-sectional study was made of the REC issues published between January 2011 and December 2020. For each article we recorded the doi identifier, the year of publication, the type of article, the number of authors, the number of female authors, and the number of women with preferential authorship. Preferential authorship was defined as first signing author, corresponding author or last author. A gender-based analysis of the number of authors, the type and year of publication and preferential authorship was carried out. Female participation was calculated from the female/male ratio, with an analysis of the trend observed over the years. Results: Of 2859 articles documented, 4275 signing authors were women and 12, 061 were men. 699, 548 and 481 women were the first, corresponding and the last author, respectively. Table 1 shows the percentage of articles in which a woman was a preferential author, as well as the percentage of women that would have to be present in the general population to cancel statistical significance. The number of articles in which a woman was the first or the corresponding author was seen to increase (p=0.008 and p=0.002, respectively), while no significant changes were observed in relation to last authorship (p=0.09). The percentage of articles in which at least one woman held at least one of the three preferential authorship positions tended to increase over time (p=0.056). In the year 2011, a total of 90 articles out of 252 (35.7%) had at least one woman among the three preferential authors, while in the year 2020 the figure was 123 out of 296 (41.6%) (Figure 1). Conclusions: Although the participation of female authors in the scientific production of the REC has increased during the last decade, authorship gender inequalities persist. Funding Acknowledgement: Type of funding sources: None.